Effects of inspiratory muscle training (IMT) on weaning outcomes in mechanically ventilated adult patients: an integrative review (Research, Society and Development, 2022)
Introduction: During prolonged stay under mechanical ventilation, a variety of respiratory and neuromuscular complications can occur, which compromise the weaning process. Having IMT as a method of increasing strength and inspiratory muscle resistance, it is suggested to be favorable for successful weaning. Objective: To review the effects of IMT on weaning results in mechanically ventilated adult patients. Methodology: This is an integrative review, using the electronic databases: PubMed, Scielo and PEDRO, referring to a period of 10 years (2012-2022), data were collected in 5 articles and subsequently classified, summarized and aggregated. Results: By establishing intervention protocols and due follow-up, it is possible to obtain positive results when using IMT with a linear load device in patients under mechanical ventilation, resulting in an increase in MIP, possible reductions in hospitalization time and successful weaning. Conclusion: The IMT obtained using a device with threshold loading has significant benefits for patients weaning from mechanical ventilation in the ICU.